Math, asked by Peachie, 1 year ago

Solve the quadratic equation 9x2 + 6x = 4 by using quadratic formula.
Solution : 9x2 + 6x - 4 = 0 ..... General form
ia = 9; b = 6 ; c = -4 ..... comparing with general form
Quadratic Formula,
-bt /
Formula
2a
-61
.... putting the values of a, b, c
2 x 9
-6th
simplifying
18
6
I
simplifying further
18
-1 √5
X=
by taking out common factor 6 and
cancelling with denominator​

Attachments:

Answers

Answered by santy2
56

Answer:

x = [-1 ±√5] / 3

Step-by-step explanation:

Let's write down the quadratic equation below:

9x² + 6x - 4 = 0

General quadratic formula is:

x = [-b ±√b² - 4ac]/2a

In this case:

a = 9, b = 6, c = -4

Doing the substitution we have:

x = [-6 ±√6² - 4 × 9 × (-4)] / 2 × 9

x = [-6 ±√180] / 18

x = [-6 ±√(36 × 5)] / 18

x = [-6 ± 6√5] / 18

x = [6(-1 ±√5)]/18

Simplifying we have:

x = [-1 ±√5] / 3

Answered by tejashree1031
50

Answer:

Hope it helps you guys

Mark me as Brainiest

All the best

Attachments:
Similar questions